Towards sustainable cities: about redundancy, voids and the potentials of the land. Issue 3 (10th December 2019) - Roggema, Rob
Abstract : Purpose: With future (extreme) change ahead of us, there are many serious problems humankind has to face. The pace of mitigating climate change through an energy transition to renewables is slow, global mean temperature is increasing and sea level seems to rise at an accelerated pace. This puts many livelihoods at risk and communities have to face an uncertain future. Therefore, continuing the way contemporary cities are developing and developed is not an option. The new normal should also be reflected in urbanism. The paper aims to discuss these issues. Design/methodology/approach: In this paper, the answer to this question is sought in understanding traditional attitudes to living and their relation to the land. How these cultures have been capable of coping with disruptions lies in the way their mental paradigm respects their environment. A more resilient future can be achieved when the traditional values of the relation of societies with the land they live on are considered important and indigenous knowledge and perspectives are used to design cities. Findings: Current society seems to have forgotten what it means and how to put into practice sharing resources and space, giving back more to the environment than used to live. Also, mankind seems to be lacking the ability to move and search for the potentials where to live. Furthermore, choosing to live in safe places, hence being less vulnerable for disruptions, is a principle that has long been neglected. These characteristics of traditional cultures are translated in four principles that are valuable in design processes: first, making use of the energy and power a disaster might bring and turning it into an advantage; second, using imagination to anticipate an unknown future; third, accommodating all paces of urban change; and fourth, designing redundancy for flexibility. The use of these principles is illustrated in three Sydney-based examples. Originality/value: The link between indigenous knowledge and current urban design practice is new.